Sourcing Data from Wikipedia for the Study of Language Contact: the csbwiki - Borges, Robert (2022)
Contact-induced language change is pervasive in contexts involving historically minoritized languages, where socialcontexts are not particularly conducive to equitable intergroup relations. Empirically driven studies involving theselanguage contexts allow us to more thoroughly understand the social and cognitive processes that lead to languagechange. Paradoxically, empirical data on minoritized languages is relatively scarce and expensive to generate. But inthe digital age we have the ability to look beyond the traditional data types used in language studies, like spoken datagathered under fieldwork conditions, literature, etc. In this paper, I will explore the potential utility of user-createdwiki data in investigating Polish influence on the Kashubian language.
Keywords: contact-induced language change; wiki data; Kashubian; corpus linguistics; vowel alternation